2008
DOI: 10.1002/jmv.21239
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and clinical impact of occult hepatitis B infection in patients with biopsy proven chronic hepatitis C: A multicenter study

Abstract: Occult hepatitis B virus (HBV) infection in patients with chronic hepatitis C has been found associated with severe liver damage, low response to interferon treatment and increased risk of developing HCC. However, doubts remain on its clinical impact and the sensitivity and specificity of its detection. HBV-DNA was sought by PCR in plasma, peripheral blood mononuclear cells (PBMCs) and liver compartments of 89 patients with biopsy proven chronic hepatitis C, using sets of primers for core ("c"), surface ("s"),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Therefore, PBMC may be an alternative source to liver biopsy for detection of an occult HBV infection. This result also was comparable to Sagnelli et al study who showed that nearly a half of HCV patients with detectable HBV-DNA in PBMCs had negative results in plasma (23 vs. 12 cases) (23). Presence of occult HBV has been reported in association with the presence of markers of HBV exposure (anti-HBc ± anti-HBs).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, PBMC may be an alternative source to liver biopsy for detection of an occult HBV infection. This result also was comparable to Sagnelli et al study who showed that nearly a half of HCV patients with detectable HBV-DNA in PBMCs had negative results in plasma (23 vs. 12 cases) (23). Presence of occult HBV has been reported in association with the presence of markers of HBV exposure (anti-HBc ± anti-HBs).…”
Section: Discussionsupporting
confidence: 87%
“…But we found no correlation between the presence of anti-HBc and prevalence of HBV-DNA in HBsAg-negative and HCV positive patients, this was compatible with some studies (3, 24). However, other studies showed higher prevalence of occult HBV among individuals seropositive for anti-HBc and/or anti-HBs, especially those with the presence of anti-HBc alone, compared with patients who had not positive results for anti-HBc and anti-HBs (1, 17, 23). The clinical significance of occult HBV is still not understood and the overall trend in the literature shows inconsistent results.…”
Section: Discussionmentioning
confidence: 83%
“…However, patients with “isolated” anti-HBc were found to have a significantly higher risk of HCC than the anti-HBs/anti-HBc-positive, most probably because these subjects showed more frequently an occult HBV infection in the liver. In fact, in our previous observation HBV DNA can be detected in plasma, peripheral blood mononuclear cells, or liver tissue of 80% of patients with “isolated” anti-HBc and of 60% of the anti-HBs/anti-HBc-positive, [14] suggesting a prolonged exposure to occult HBV replication that may favor the onset of HCC. However, it may also be hypothesized that circulating anti-HBs may prevent the risk of HCC, most probably by controlling HBV replication, as already suggested.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Reactivation of occult HBV infection has been more frequently observed in patients showing anti-HBc as the only HBV marker (“isolated” anti-HBc). [14] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation